Attitude As Dominant Predictor Of Pregnancy Anemia Incidence: A Cross-Sectional Analysis In Urban Jakarta - Siti Jumhati; Erwinsyah Hasyim Harahap; Sasqia Dwi Putri Meliani (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Anemia remains a major public health problem during pregnancy, affecting approximately 40% of pregnancies globally and 27.7% of pregnant women in Indonesia. Although maternal knowledge and attitudes are considered important behavioral factors, evidence regarding their association with anemia among pregnant women in urban Indonesian settings remains limited. Method: A cross-sectional analytic study was conducted from July to August 2025 involving 60 pregnant women attending urban health facilities in East Jakarta. Knowledge and attitudes were assessed using validated questionnaires (Cronbach’s α=0.79–0.82). Anemia status was determined using a Sahli hemoglobinometer, with hemoglobin levels <11 g/dL classified as anemia. Data were analyzed using Chi-square tests and binary logistic regression with the Forward Likelihood Ratio method. Result: The prevalence of anemia was 45.0% (27/60). Bivariate analysis showed that negative maternal attitude was significantly associated with anemia (OR=8.50; 95% CI: 2.10–34.20; p=0.002), whereas poor knowledge was not significantly associated (p=0.152). In multivariate analysis, negative maternal attitude remained significantly associated with anemia (aOR=7.85; 95% CI: 2.10–29.35; p<0.001). The final model explained 68.4% of the variance (Nagelkerke R²) and demonstrated good calibration (Hosmer–Lemeshow p=0.742). Conclusion: Negative maternal attitude was significantly associated with anemia among pregnant women in this study. These findings suggest that maternal attitudes may be an important factor to consider in antenatal health promotion and anemia prevention programs. Further longitudinal studies are needed to clarify the direction and causal nature of this relationship.